Dampak Model Pembelajaran Reciprocal Teaching terhadap Kemampuan Berpikir Kritis Siswa SMA - Khoirunnisa Lili Rahmawati (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to determine the effect of the reciprocal teaching learning model on the critical thinking skills of SMAN 4 Madiun students. The method used is Pretest-Posttest Control Group Design. The results showed that the tcount obtained was 133,955 (> ttable 2,080). In conclusion, there is an effect of applying the reciprocal teaching learning model to the critical thinking skills of SMAN 4 Madiun students. Keywords: Critical Thinking, Learning Model, Reciprocal Teaching